CONSTRUÇÃO DAS IDENTIDADES SOCIAIS DE RAÇA COM INTERSECÇÃO DE CLASSE NOS LIVROS DIDÁTICOS DE INGLÊS DO ENSINO MÉDIO APROVADOS PELOS PNLDs 2012 e 2015 - Dambrós, Lilian Paula (2016)
This research entend to understand how the textbooks help to construction of social identities of race with class intersection. It has how goals analyzing four PNLD’s collections, of the year 2012 of high school and three PNLD’s collections, 2015, also high school, in order to understand how social identities of race, class-intersection, are represented these textbooks through speeches and multiliteracies. By analyzing the textbooks sought to answer the following questions: how the textbooks of English, suggested by PNLDs (2012 and 2015), build social identities of race and class? As the black racial identity and white racial identity are represented through literacies and multiliteracies resources of textbooks? The textbooks of English high school suggested by PNLDs 2012 and 2015, use the multiliteracies resources, enable reflections mentioned in Law 10,639 / 03? The theoretical contributions, which were the theoretical and methodological basis for this research, are supported in a literature review of studies that have been conducted with textbooks, like Ferreira (2012) and Barros (2013); about the literacies and multiliteracies bring to the discussion Kleiman (1995 and 2005), Kalantzis and Cope (2008) and Street (2014). To discuss the representation and I make use of identity Hall (2000), Bauman (2005) and Block (2006). This research also aims to reflect on the linguistic and educational policies such as PCN-LE (BRAZIL, 1998), OCEM-LE (2006), DCE-LE (PARANÁ, 2008), which tells the PNLD (BRAZIL, 2012 ) and the Federal Law 10.639 / 03 (BRAZIL, 2004). As for the methodology, was documentary analysis of linguistic and educational policies and written speeches and images produced in the English language textbooks, according to Moita Lopes (1996), Ferreira (2014), Herbele (2004), Wodak (2004) and Rojo (2009, 2012), taking into account the issue of multiliteracies. Also used the critical discourse analysis, according to Van Dijk (2012). After my analysis, I got the following final remarks: it is necessary that the teacher’s training be continuous, thus improving their knowledge about the existing racial prejudice in textbooks, the dominant ideologies brought through multiliteracies these and realize how much the textbooks influence the construction of identities of students. Teachers also need to encourage their students to a critical look at the differences, even if they are not being well represented by textbooks have analyzed because these are full of prejudice and ideologies that exclude black and poor, including the under representation of the characters, the representation of the less complex characters by means of stereotypes with defined spaces and subordinate manner. I hope, with this work, more high school teachers to understand the speeches conveyed to textbooks and start to reflect critically on the policies of the textbook as well as publishers and authors of such books.